Meta-Analysis: Factors Reducing Health Workers' Willingness to Leave Work - Hidayat, Fany Nurul Fawzi; Raharjo, Setyo Sri; Ichsan, Burhannudin (Journal of Health Policy and Management, 2025)
Background: Employees are the most important human resource in a company because they have a direct influence on institutional operations in achieving organizational goals. The main problem in health service management is a shortage of health workers due to turnover or intention to leave work. This research aims to analyze the factors that reduce the desire to leave among health personnel. Subjects and Method: This research uses a meta-analysis based on PICO as follows; population: health workers; intervention: satisfied autonomy, good working environment, length of service > 5 years, low workload; comparison: autonomy not satisfied, poor working environment, length of service < 5 years, high workload; outcome: intention to leave work. Data was obtained from the PubMed, Google Scholar, Science Direct databases published from 2013-2022. The keywords in the article search are "Autonomy", "Work Environment", "Work Experience", "Workload", "Intention to Out", "Turnover Intention". "Cross Sectional". Article selection used PRISMA Flowchart and results were analyzed using Review Manager 5.4 software. Results: This study was conducted on 14 articles from Ethiopia, Ghana, California, Peru with a sample size of 9,555 professional health workers. Meta-analysis results concluded that satisfied work autonomy (aOR=0.22; CI 95%=0.06 to 0.85; p=0.030), low workload (aOR=0.60; CI 95%=0.46 to 0.78; p<0.001), had the desire out of work low. The meta-analysis results of the work environment were good (aOR=0.51; CI 95%=0.23 to 1.14; p=0.100), work experience >5 years (aOR=0.51; CI 95%=0.23 to 1.14; p=0.100) was not significantly influenced. Conclusion: Satisfied job autonomy and low workload reduce the intention to leave work among health workers. Health workers' desire to leave work is not significantly influenced by work experience or work environment.